(untitled) (Medico Legal Update, 2020)
The present research is an empirical effort made to study how the Emotional Intelligence factors influence on the interpersonal problems of adults. The sample-size is 500 comprising 200 teachers, 150 IT professionals and 150 nurses. The stratified random sampling method is adopted. The age ranges from 22 to 50 (Mean Age = 31.95). The research is executed with non-clinical samples. The tools adopted are: (1) Emotional Intelligence scale4 and (2) Inventory of the Interpersonal Problems8 (IIP-32). The participants are contacted individually by the researcher and data is obtained with the help of the above mentioned tools. The descriptive statistics and correlation are used for the statistical analyses. Results indicate that the dimensions of interpersonal problems are negatively correlated and it is statistically significant with the dimensions of emotional intelligence at the 0.01 level of significance as well as at the 0.05 level of significance.This finding supports the understanding and the development of effective strategies in psychotherapy.